Anti-human neutrophil antigen-1d specificity is frequently observed in anti-human neutrophil antigen-1b alloantisera - Grabowski, Claudia; Reil, Angelika; Bux, Jürgen; Bayat, Behnaz; Sachs, Ulrich J.; Justus Liebig University Giessen (My University, 2022)
Background: Four amino acids are involved in epitope formation of human neutrophil antigens (HNA)-1 alleles, located at positions 36, 65, 78, and 82. HNA-1a and HNA-1b alloantibody epitopes were recently characterized. The HNA-1b allele also carries the HNA-1d epitope p.78A&p.82N. The current study aimed to identify compound antibody specificities in HNA-1b alloantisera, especially the presence of anti-HNA-1d. Study Design and Methods: For investigation of binding epitopes for HNA-1b alloantibodies, cells stably expressing different HNA-1 alleles were generated and tested against previously well-characterized HNA-1b antisera (n = 11) in an antigen capture assay. Sera with p.82N specificity or p.36S and p.82N specificity were additionally analyzed using adsorption and elution methods. Results: Three amino acids, p.36S, p.78A, and p.82N, are involved in epitope formation of HNA-1b. The following specificities were identified in 11 HNA-1b alloantisera: p.36S (6/11), p.82N (9/11), and p.78A&p.82N (8/11), of which p.36S was identified as a sole entity in 2/11, whereas 9/11 antisera contained a polyspecific mixture of anti-p.36S, p.82N (1/11), and anti-p.78A&p.82N in combination with anti p.82N (5/11) or compound specificities of anti-p.36S, p.82N, and p.78A&p82N (3/11). In seven of eight antisera with p.82N specificity, anti-p.78A&p.82N was detected. Discussion: Analysis of HNA-1b antisera indicates compound specificities for HNA-1b alloantibodies with a high variation between HNA-1b immunized individuals. Amino acids p.36S, p.82N, and p.78A&p.82N are necessary for HNA-1b epitope formation. The HNA-1d epitope is recognized by 73% (8/11) of HNA-1b immunized individuals.
Keywords: CD16b; HNA-1b alloantibodies; HNA-1d epitope; ddc:610